2018
DOI: 10.1021/acsnano.8b01422
|View full text |Cite
|
Sign up to set email alerts
|

Structure–Stability–Function Mechanistic Links in the Anti-Measles Virus Action of Tocopherol-Derivatized Peptide Nanoparticles

Abstract: Measles remains one of the leading causes of child mortality worldwide and is re-emerging in some countries due to poor vaccine coverage, concomitant with importation of measles virus (MV) from endemic areas. The lack of specific chemotherapy contributes to negative outcomes, especially in infants or immunodeficient individuals. Fusion inhibitor peptides derived from the MV Fusion protein C-terminal Heptad Repeat (HRC) targeting MV envelope fusion glycoproteins block infection at the stage of entry into host c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 58 publications
0
18
0
Order By: Relevance
“…We have previously demonstrated that lipid conjugation of HRC-derived inhibitory peptides markedly increases antiviral potency and in vivo half-life (13)(14)(15)(16), and used this strategy to create entry inhibitors for prophylaxis and/or treatment of human parainfluenza virus type 3, measles virus, and Nipah virus infection (14,15,(17)(18)(19)(20). Both dimerization and peptide integration into cell membranes proved key to ensure respiratory tract protection and prevent systemic lipopeptide dissemination (16,18).…”
Section: Main Textmentioning
confidence: 99%
“…We have previously demonstrated that lipid conjugation of HRC-derived inhibitory peptides markedly increases antiviral potency and in vivo half-life (13)(14)(15)(16), and used this strategy to create entry inhibitors for prophylaxis and/or treatment of human parainfluenza virus type 3, measles virus, and Nipah virus infection (14,15,(17)(18)(19)(20). Both dimerization and peptide integration into cell membranes proved key to ensure respiratory tract protection and prevent systemic lipopeptide dissemination (16,18).…”
Section: Main Textmentioning
confidence: 99%
“…The hydrodynamic radius (R H ) of Ctn [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] particles was monitored over 12 hours at 500μM final concentration using a Malvern Zetasizer Nano ZS (Malvern, UK) in particle size analysis mode as previously described. 41 TABLE 1 Design rationale and synthesis data of Ctn [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] analogs in this study Note. Five-residue sequence blocks spanning the Lys-rich, helical-prone domain (red), or the hydrophobic domain (blue) were combined in different manners to give analogs 1 to 3.…”
Section: Dynamic Light Scattering (Dls)mentioning
confidence: 99%
“…The atomistic structures were converted to the corresponding CG models using the martinize.py script [41], for subsequent simulation under the GROMACS 5.1 package [42]; (2) a 4-unit PEG linker, built from an existing CG model of PEG [43] was appended to the peptides. To simplify the CG modeling maleimide was not taken into account and was instead replaced by three PEG beads in the final models (for a total 7-unit PEG linker); (3) for the Chol-and Toc-conjugated peptides the previously described Chol [44] or Toc [45] models were appended to the linker segment. Parameters for linker connections followed those of the Cys sidechain particle that they replaced.For the aggregation simulations, boxes containing 8 peptide molecules and either 23075 Martini waters, 271 Na+ and 255 Cl-molecules for monomeric peptides, or 23051 Martini waters, 295 Na+ and 255 Cl-molecules for dimeric peptides, were used.…”
Section: Coarse-grained Molecular Dynamics Simulationsmentioning
confidence: 99%
“…The molecular level effects of the Leu-to-Trp substitution in the self-assembly process remained unclear after the experiments above. We had previously shown that CG molecular dynamics can capture important features of inter-molecular association during the aggregation process of HRC5 and HRC6 peptides in a µs range timescale [45]. The same CG methodology was used to analyze the assembly of the HRC-L454W peptides.…”
Section: Tryptophan Substitution Favors Inter-cluster Interactions Inmentioning
confidence: 99%
See 1 more Smart Citation